Corrosion-resistant non-noble metal electrodes for PEM-type water electrolyzer. (11th November 2021) - Tajuddin, Aimi Asilah Haji; Elumalai, Ganesan; Xi, Zeyu; Hu, Kailong; Jeong, Samuel; Nagasawa, Kensaku; Fujita, Jun-ichi; Sone, Yoshitsugu; Ito, Yoshikazu
Abstract: Developing cheap and highly durable non-noble metal catalysts for water electrolysis to sustainably produce hydrogen as alternatives to platinum-based catalysts is essential. Herein, we report graphene-encapsulated NiMo alloys as acid-stable non-noble metal catalyst electrodes. The graphene-encapsulated NiMo cathode showed a highly stable performance in the potential cycling test (10, 000 cycles) from 0 to 5.0 A cm −2 and 100 h of durability at a 2.2 V constant cell voltage. A balance between catalytic activity and corrosion in acidic environments was achieved by tuning the number of N-doped graphene layers. Through their application in a full-cell PEM-type water electrolyzer, we verify that noble metal catalysts can be replaced by non-noble metal catalysts. Such cheap acid-stable non-noble metal electrodes have promising practical applications in PEM-type water electrolysis. Highlights: Preparation of graphene-encapsulated NiMo cathode catalysts. Performance validation of non-noble metal catalysts in PEM-type water electrolysis. For replacement of conventional noble metal catalysts that are expensive. Various applications involving acidic environments.